Peran Pusat Pembelajaran Keluarga dalam Kontrol Parenting Era Digital di Kelurahan Bendul Merisi Kota Surabaya - Mohammad Rexy Prayitno; Bayu Priambodo (IAI Nasional Laa Roiba Bogor, 2024)
The Family Learning Center plays a significant role in developing parenting control within a family to prevent negative impacts that could harm the moral values of the nation's successors. Through programs implemented by the central government, the Family Learning Center provides an understanding to the citizens about the importance of monitoring their families. This research focuses on the application of the Social Change and Communication Theory by Rogers & Kincaid. Data analysis is conducted using the interactive model by Miles and Huberman in a gradual and interactive manner on the predetermined data. The Family Learning Center plays a crucial role in improving the well-being of a family. By utilizing direct communication methods at the neighborhood community hall (RW), the program has been successfully completed according to the set targets.